2022
DOI: 10.2334/josnusd.21-0282
|View full text |Cite
|
Sign up to set email alerts
|

Gingival crevicular fluid microRNA associations with periodontitis

Abstract: Purpose: The present study was performed to assess the associations of gingival crevicular fluid (GCF) microRNAs miR-140-3p, miR-145-5p, miR-146a-5p, and miR-195-5p with periodontitis (PD) and to evaluate the possible influence of rheumatoid arthritis (RA) in this context. Method: GCF samples were collected from 134 individuals with PD and 76 periodontally healthy individuals, with or without RA. After miRNA extraction from GCF, the levels of miR-140-3p, miR-145-5p, miR-146a-5p, and miR-195-5p were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The multivariate linear regression analysis aimed at identifying possible predictors of GCF miRNAs expression highlighted that, among the analyzed confounders, the extent of periodontitis (PISA) represented one of the main significant predictors of several GCF miRNAs expression. In agreement with the present results, it has been previously shown that the local miRNAs upregulation may be directly correlated to the extent of periodontitis 36 and also that the severity of periodontitis could in turn influence the serum (miRNA‐199a‐5p) and local levels of several miRNAs in both gingival tissues (miRNA 199a‐5p, ‐483‐5p, ‐3198, ‐4299), GCF (miRNA‐140‐3p, ‐145‐5p, 146a‐5p, ‐3198, ‐4299) and saliva (miRNA‐381‐3p) 18,37 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The multivariate linear regression analysis aimed at identifying possible predictors of GCF miRNAs expression highlighted that, among the analyzed confounders, the extent of periodontitis (PISA) represented one of the main significant predictors of several GCF miRNAs expression. In agreement with the present results, it has been previously shown that the local miRNAs upregulation may be directly correlated to the extent of periodontitis 36 and also that the severity of periodontitis could in turn influence the serum (miRNA‐199a‐5p) and local levels of several miRNAs in both gingival tissues (miRNA 199a‐5p, ‐483‐5p, ‐3198, ‐4299), GCF (miRNA‐140‐3p, ‐145‐5p, 146a‐5p, ‐3198, ‐4299) and saliva (miRNA‐381‐3p) 18,37 …”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the present results, it has been previously shown that the local miRNAs upregulation may be directly correlated to the extent of periodontitis 36 and also that the severity of periodontitis could in turn influence the serum (miRNA-199a-5p) and local levels of several miRNAs in both gingival tissues (miRNA 199a-5p, -483-5p, -3198, -4299), GCF (miRNA-140-3p, -145-5p, 146a-5p, -3198, -4299) and saliva (miRNA-381-3p). 18,37 One of the reason may be due that periodontitis contributes, through its chronic pathogenic biofilm burden, to a continuous negative stimulus on the local host response, with a further secretion of hs-CRP, NO and many other inflammatory mediators in a mechanism locally regulated by different miRNAs, 38…”
Section: Discussionmentioning
confidence: 99%
“…Gingival crevicular fluid (GCF) is a fluid secreted by the gingival sulcus of teeth, which can be used to monitor the development of CP to adopt a targeted treatment plan, and a large number of miRNAs in GCF are identified and can modulate the CP immune response, 12 for example, miR-140-3p, miR-145-5p and miR-195-5p. 13 …”
Section: Introductionmentioning
confidence: 99%
“…These tools might allow us to have access to higher accuracy of target selection and improve the sensitivity of the prediction on circRNA regulations. At the same time, integrating sequencing profiling with clinical information could help broaden the knowledge for a better understanding of periodontitis pathogenesis 35–38 …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, integrating sequencing profiling with clinical information could help broaden the knowledge for a better understanding of periodontitis pathogenesis. [35][36][37][38] The purpose of this study was to assess the perturbation in circular RNA expression profiles by high-throughput sequencing and interrogate the association of aberrantly expressed circRNAs and the pathology of periodontitis. RT-qPCR and correlation between circRNA expression levels and clinical parameter probing depth (PD) were conducted to strengthen the reliability of prediction.…”
Section: Introductionmentioning
confidence: 99%